Clinical factors leading to a change in management in chronic hepatitis B patients managed in a tertiary setting. Issue 2 (9th February 2020) - Koh, Yu Han; Ong, Joanne Hui Yi; McCartney, Erin; Morgan, Joanne; Narayana, Sumudu; Tse, Edmund
Abstract: Background: Newer antiviral agents for chronic hepatitis B (CHB) are highly effective, with minimal risks of complications and development of resistance. Aim: To identify the proportion of patients with CHB on treatment who will not require alteration of management and the clinical factors of those who will require closer monitoring. Methods: Patients with CHB who were on entecavir and/or tenofovir between January 2011 and December 2016 were retrospectively studied. According to the initial treatment plan provided by the managing physician, any deviation in the interval of follow up, choice of investigations and alteration of medical therapy were considered a change in CHB management. We also evaluated the predictability of these changes, factors associated with higher frequency of change and the additional cost of managing stable patients with CHB in a tertiary setting. Results: Of the patients, 75.7% ( n = 87/115) did not have a change in CHB management; 85.6% of the changes in management were predictable based on liver function tests, hepatitis B virus DNA polymerase chain reaction levels and liver ultrasound. Interpreter use (OR (95% CI) = 2.41 (1.01–5.76)), liver cirrhosis (OR (95% CI) = 4.11 (1.44–11.75)) and immunosuppression (OR (95% CI) = 3.81 (1.2–12.06)) were associated risk factors. Overall, there was an incremental annual cost of AU$60 166 to manage patients who did not require alteration of their CHB management in our institution. Conclusion: The majority of stable CHB patients on highly potent antiviral treatment do not require alteration of management. While additional investigations are required, this study highlights the potential for a shared primary care approach in highly selected CHB patients.